Quem somos eu? : estudo etnografico sobre processos de construção de personas políticas - Silva, Renata Lopes da (2013)
This work, through a research bibliography and interviews, seeks to examine over the process of collective construction of politic person with emphasis in deputies of the estate of Rio Grande do Sul. The initial part of the dissertation consists of an exhibition on the notion of personhood and identity, and if it tries to clarify the concept that was adopted in this work. Further, it seeks to clarify the topic and its relevance through data collected in field research. Will be explored the everyday of the politic person, and observed the methods used to building his character. The emphasis is the advisors actions that get influence on politic performance. Will be used the method of participant observation. Methodological procedures in order to prepare the Dissertation Proposal are discussed, stressing the research question and the hypothesi to be tested. Also, is discussed the issues, establishing the initial steps for those willing to deepen into it.